2018
DOI: 10.3390/nu10111793
|View full text |Cite
|
Sign up to set email alerts
|

Gut Permeability Might be Improved by Dietary Fiber in Individuals with Nonalcoholic Fatty Liver Disease (NAFLD) Undergoing Weight Reduction

Abstract: (1) Introduction: Zonulin (ZO) has been proposed as a marker of intestinal permeability. Only a few studies have analyzed to date how diet influences the serum concentration of ZO among patients with non-alcoholic fatty liver disease (NAFLD). We performed a six-month dietetic intervention to evaluate the association between fiber intake and ZO concentration in 32 individuals with NAFLD. (2) Methods: Fiber content in the diet was estimated by Food Frequency Questionnaire (FFQ) and by analyzing 72-h nutritional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
47
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(54 citation statements)
references
References 31 publications
3
47
0
4
Order By: Relevance
“…Only few, smaller observational studies reported that patients with NAFLD consume fewer vegetables and less dietary fiber than controls . Randomized intervention studies have shown that fiber intake improves liver enzymes and noninvasive NAFLD scores among participants with NAFLD . We found a significant inverse trend between fruit intake and NAFLD, and a previous study showed that fiber from fruits has a favorable effect on liver enzymes among obese individuals .…”
Section: Discussionsupporting
confidence: 65%
“…Only few, smaller observational studies reported that patients with NAFLD consume fewer vegetables and less dietary fiber than controls . Randomized intervention studies have shown that fiber intake improves liver enzymes and noninvasive NAFLD scores among participants with NAFLD . We found a significant inverse trend between fruit intake and NAFLD, and a previous study showed that fiber from fruits has a favorable effect on liver enzymes among obese individuals .…”
Section: Discussionsupporting
confidence: 65%
“…Intestinal mobility has also been linked to the intestinal permeability, a potential cofactor in disease progression of NAFLD in both animal models and humans [24]. Consequently, dietary interventions focusing on increasing dietary fiber content were able to demonstrate a decrease in surrogates of intestinal permeability in patients suffering from NAFLD [25].…”
Section: Discussionmentioning
confidence: 99%
“…Dietary intervention studies are limited; however, one study suggests an increase in dietary protein is associated with elevated zonulin and inflammation . Furthermore, it has been demonstrated that an increase in dietary fibre reduces zonulin . While alcohol withdrawal is associated with a reduction of IP with a greater result seen in patients with a high BMI .…”
Section: Discussionmentioning
confidence: 99%
“…84 Furthermore, it has been demonstrated that an increase in dietary fibre reduces zonulin. 85 While alcohol withdrawal is associated with a reduction of IP with a greater result seen in patients with a high BMI. 54 Based on these findings, dietary and lifestyle habits may present a key clinical feature that healthcare professionals may utilise in identifying patients at risk of altered IP.…”
Section: Dietary and Lifestyle Habits And Intestinal Permeabilitymentioning
confidence: 99%